Femoral Arteriovenous Grafts for Hemodialysis: Retrospective Comparison With Upper Extremity Grafts and Fistulas. Issue 1 (14th July 2017) - Dumaine, Chance; Espino-Hernandez, Gabriela; Romann, Alexandra; Luscombe, Rick; Kiaii, Mercedeh
Background: Femoral arteriovenous grafts are rarely used to provide vascular access for dialysis patients. This is likely due, in part, to historically high rates of graft loss from infection and thrombosis. However, for selected patients who have exhausted all access options in the upper extremity, femoral grafts can provide additional sites for access creation and may be preferred over central venous catheters. Objective: We sought to demonstrate that femoral grafts can provide a reliable and safe alternative to central venous catheters for selected patients. Methods: A single-center retrospective review in Vancouver, Canada, from April 1, 2008, to March 31, 2012, was conducted. All patients with new arteriovenous access (grafts and fistulas) created during the study period were included in the study population and followed for a minimum of 2 years. Comparisons of patency (primary, secondary, and functional) and complications (infectious and noninfectious) were made between the different access types. Results: Thirteen patients with femoral grafts were compared with 22 patients with arm grafts and 384 patients with fistulas. Femoral grafts had higher rates of thrombosis (46% with a thrombotic event) and a higher requirement for interventions (1.3 angioplasties and 0.12 thrombolytic procedures per patient per year). However, compared with arm grafts, femoral grafts had superior secondary and functional patency. No difference in patency was seen when comparing femoral grafts with upper extremity fistulas. Only 2 patients with femoral grafts required antibiotics for infection, and no grafts were lost to infection. Conclusions: For patients with limited access options remaining, femoral grafts may provide an additional form of vascular access before resorting to catheter use. Our study shows that with appropriate patient selection, femoral grafts have low infection rates and patency that is comparable with other access types.